2014
DOI: 10.1089/cell.2014.0016
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-34c Expression in Donor Cells Influences the Early Development of Somatic Cell Nuclear Transfer Bovine Embryos

Abstract: The essence of the reprogramming activity of somatic cell nuclear transfer (SCNT) embryos is to produce normal fertilized embryos. However, reprogramming of somatic cells is not as efficient as the reprogramming of sperm. In this report, we describe the effect of an inducible, specific miR-34 microRNA expression in donor cells that enables a similar level of sperm:transgene expression on the early development of SCNT embryos. Our results showed that donor cells with doxycycline (dox)-induced miR-34c expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Previous study has shown that injection of sperm-borne miR-34c inhibitor into zygotes could inhibit DNA synthesis and significantly suppress the first cleavage division in mouse 13 . In bovine, we also observed that high expression of miR-34c in somatic cell donor cells affected cleavage and development of SCNT embryos 28 . As part of the same family, miR-34c and miR-449b share the same seed sequence and many target genes 14 , 35 .…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Previous study has shown that injection of sperm-borne miR-34c inhibitor into zygotes could inhibit DNA synthesis and significantly suppress the first cleavage division in mouse 13 . In bovine, we also observed that high expression of miR-34c in somatic cell donor cells affected cleavage and development of SCNT embryos 28 . As part of the same family, miR-34c and miR-449b share the same seed sequence and many target genes 14 , 35 .…”
Section: Discussionmentioning
confidence: 69%
“…Bovine fetal fibroblast cells were cultured as described previously 28 . The head and viscera of 35-day-old fetuse were discarded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it was thought that only oocytes contained regulators of embryonic development. However, a large body of evidence suggests that sperm also contains signi cant amounts of proteins, mRNAs, tRNAs, tsRNAs, PIWI-interacting RNAs, and miRNAs, which have recently been shown to have important effects on embryonic development [2,3,4,5]. Many post-transcriptional regulatory factors, such as miRNAs, can be delivered into oocytes during fertilization.…”
Section: Introductionmentioning
confidence: 99%